2015
DOI: 10.1002/fsn3.249
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and blanch‐assisted drying of white yam (Dioscorea rotundata)

Abstract: The effect of microwave and blanch pretreatments on the drying kinetics and quality of white yam (Dioscorea rotundata) was investigated. Yam cubes destined for hot air drying at temperatures 70–90°C were predried in a domestic microwave or blanched in hot water for 1–5 min. Microwave pretreatment time had a positive significant effect on drying rate but both pretreatments had a negative influence on the ascorbic acid content and the nonenzymatic browning. The optimum drying conditions were a microwave pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
(24 reference statements)
5
17
1
Order By: Relevance
“…Hence, the samples blanched in microwaves for 3 min recorded lower final moisture content than the untreated samples. This observation corroborates with the findings Abano and Amoah (2015), who reported that as microwave pretreatment time increased from 1 to 5 min, moisture removal also increased during microwave assisted drying of white yam. where MB time is microwave blanching time (min) and BSS ratio is brine solution to sample ratio.…”
Section: Analysis Of Data and Process Optimizationsupporting
confidence: 92%
“…Hence, the samples blanched in microwaves for 3 min recorded lower final moisture content than the untreated samples. This observation corroborates with the findings Abano and Amoah (2015), who reported that as microwave pretreatment time increased from 1 to 5 min, moisture removal also increased during microwave assisted drying of white yam. where MB time is microwave blanching time (min) and BSS ratio is brine solution to sample ratio.…”
Section: Analysis Of Data and Process Optimizationsupporting
confidence: 92%
“…Microwave pretreated samples were transferred to a hot air cabinet dryer (GENLAB Oven, Model SDO225, 240 AC 1PH, 540 × 920 × 440 mm, 2 kW) set at temperature of 70°C and air circulation of 0.5 m/s. This temperature was chosen based on previous optimization studies [ 14 ]. The dryer was run idle for 1 hr earlier to the drying experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A method previously reported by [ 14 ] was used to evaluate the nonenzymatic browning of the dried mango slices. The extent of browning was measured as absorbance at 440 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture ratio of the controlled and pretreated bitter gourd samples dried at three different temperatures are shown in Fig 1- respectively. This is due to the penetration of electromagnetic waves altering the cell wall structure and forming the pores in the tisssues thus enabling increased water diffusion from interior to surface during drying (Abano & Amoah, 2015). Ethyl oleate (EO) treatment further decreased the drying time significantly (P<0.05) to 230, 170 and 130 min dried at 50, 60 and 70ºC respectively.…”
Section: Effects Of Pretreatments On Moisture Ratio Of Bitter Gourdmentioning
confidence: 99%